Skill loss, ranking of job applicants, and the dynamics of unemployment - Stefan Eriksson (Institute for Labour Market Policy Evaluation (IFAU), 2001)
This paper investigates the consequences of skill loss as a result of unemployment in an efficiency wage model with turnover costs and on-the-job search. Firms are unable to differentiate wages and therefore prefer to hire employed searchers or unemployed workers who have not lost human capital. It is shown that if some fundamental factor in the economy changes, this will result in a lengthy adjustment process with substantial long run unemployment effects. Moreover, the model is capable of generating persistence but the amount depends on the duration of the shock itself
Keywords: E24; J64; 330; Efficiency wage; Turnover; On-the-job search; Skill loss; Persistence; Short- and long term unemployment